Analysis of Termination of Prosecution of Drug Abusers for Self-Deterrence Based on Restorative Justice (Case Study: West Jakarta District Attorney's Office) - Darmawan, R. Alif Ardi; Suwondo, Denny (Jurnal Hukum Khaira Ummah, 2025)
The restorative justice approach in resolving drug abuse cases for oneself is an alternative that emphasizes recovery and rehabilitation, not just punishment, as reflected in the implementation at the West Jakarta District Attorney's Office. The purpose of this study is to analyze the implementation of the termination of prosecution against drug abusers for themselves based on restorative justice at the West Jakarta District Attorney's Office, analyze the obstacles and solutions to the termination of prosecution against drug abusers for themselves based on restorative justice at the West Jakarta District Attorney's Office and analyze the efforts of the West Jakarta District Attorney's Office towards the termination of prosecution against drug abusers in the future. The approach method used in compiling the thesis is sociological legal research. Specifications in this study descriptive analysis. The theories used include restorative justice theory and legal system theory. The results of this study are (1)The implementation of the termination of prosecution against drug abusers for themselves based on restorative justice at the West Jakarta District Attorney's Office, shows the commitment of law enforcement institutions to prioritize a rehabilitative approach in handling drug cases. The suspect RBS, who was proven to be only a user, was not involved in a drug distribution network, and showed good faith, was positioned as an individual who deserves to be restored through rehabilitation, not imprisonment. (2) The implementation of restorative justice at the West Jakarta District Attorney's Office still faces weaknesses. In terms of legal substance, Attorney General Regulation Number 15 of 2020 provides a strong basis, but there are no clear regulations in the Criminal Procedure Code regarding the termination of prosecution based on restorative justice. The legal structure, the main challenge lies in the uneven understanding among law enforcement officers. In terms of legal culture, the community and law enforcement officers are still trapped in a retributive paradigm that prioritizes criminal penalties. For this reason, changes in the substance of the law are needed by revising Article 140 paragraph (2) of the Criminal Procedure Code, strengthening the institutional structure with training, and providing socialization about restorative justice to the community. (3) The efforts of the West Jakarta District Attorney's Office towards the termination of prosecution of drug abusers in the future by prioritizing a more humanistic legal approach through the implementation of restorative justice based on Pancasila values. By making restorative justice the main policy, forming a special RJ team, and strengthening cross-sector coordination.